The Existence Of Lego-Lego Art As The Identity And Culture Of The Alor People - Tamonob, Jeny; Relin Yosi Huka (Universitas Negeri Semarang, 2024)
Lego-lego art in Alor society today is influenced by globalization so that at the present time it is not displayed live but uses audio recordings which make the existence of the art less meaningful and meaningful to the art. The purpose of this study is to analyze what factors influence the existence of Lego-lego art in the Alor people. This research uses a qualitative approach to literature review through several scientific article literature, YouTube media and e-books about the people of Alor. The results show that the existence of Lego-lego art can be seen from its use as a means of entertainment and as a medium of learning in subjects at school to improve student character education.